Biometry of Modiolus capax (Bivalvia: Mytilidae) in Playa Ocotal, Guanacaste, Costa Rica - Cabrera Peña, Jorge (1994)
155 specirnens of mussels (Modiolus capax) were gathered during March 1993 in a subtidal hed, located in northern Ocotal, Guanacaste, Costa Rica. For each individual in the randon sample, shell length, breadth and height were measured and total weight, shell weight empty and meat weight were controlled. Analysis of data determined relationships of length to weight, length to breadth and length to height ofLt= 1.31977 Pt + 29.05478, Lt= 0.36605 D + 3.98744 and Lt= 0.50434 A + 2.73786. The mean Conditional Index for the population was 39 ± 0.07